RESERVOIR CHARACTERIZATION USING SIMULTANEOUS INVERSION TO DELINEATE HYDROCARBON RESERVOIR - Muhamad Defi Aryanto; Darsono Darsono; Julikah Julikah; Humbang Purba (Testing Center for Oil and Gas LEMIGAS, 2014)
Reservoir characterization analysis has been carried out for identifying lithology and Àuid content on TalangAkarFormation in South Sumatra Basin. Robust method that being used in this study is the simultaneous inversion which uses pre-stack gather and well log data from Puja A and Puja B. Elastic parameters resulted from simultaneous inversion are P Impedance, S Impedance and V / V ratio. Lambda-Rho parameter (lr) and Mu-Rho (mr) derived from P impedance (I ) and S impedance (I ). Lambda-Rho is sensitive to Àuid content while Mu-Rho to lithology. Area of interest in this study is Talang Akar Formation as reservoir which contains gas with Lambda-Rho (lr) between 5-15 (GPa*g/cc) and Mu-Rho (mr) 35-45 (GPa*g/cc). The ratio of P wave (Vp) and S wave (Vs) can be used as an indicator to determine Àuid saturation. Gas saturated rock has value of Vp / Vs lower than the water saturated rock. In this study, the ratio of Vp / Vs is 1.5-1.7 for gas saturated rock